The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/jac/dkq496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recA inactivation on mutagenesis of Escherichia coli exposed to sublethal concentrations of antimicrobials

Abstract: The fact that inactivation of recA reduces mutagenicity and/or increases the activity of a large number of antimicrobials supports the hypothesis that RecA inhibition might have favourable effects on antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
116
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 47 publications
12
116
3
2
Order By: Relevance
“…Likewise, inactivation of the recA gene of E. coli is known to increase bacterial susceptibility to several antibiotics (22,50). We obtained similar results in tests of the susceptibility of the A. baumannii recA mutant to different groups of antimicrobials (Table 3).…”
Section: Discussionsupporting
confidence: 74%
“…Likewise, inactivation of the recA gene of E. coli is known to increase bacterial susceptibility to several antibiotics (22,50). We obtained similar results in tests of the susceptibility of the A. baumannii recA mutant to different groups of antimicrobials (Table 3).…”
Section: Discussionsupporting
confidence: 74%
“…on May 10, 2018 by guest http://aac.asm.org/ nation (41), and the induction of mutagenic polymerases that participate in the SOS response (32,37,44). In the present work, colony staining with diaminobenzidine indicated that colonies growing on LB plates supplemented with CIP accumulated considerably more hydrogen peroxide than those developed in the absence of antibiotic (data not shown).…”
supporting
confidence: 48%
“…All of these compounds strongly induce RFP expression of the reporter. Sulfanilamide inhibits the synthesis of purines and pyrimidines and, due to imbalance of the substrates for DNA synthesis, activates the SOS response, as visualized by application of another LexA-regulated reporter, recA::gfp (39,40). The moderate induction of RFP expression by rifampin is of interest.…”
Section: Discussionmentioning
confidence: 99%